(untitled) (Research, Society and Development, 2024)
Studies on the side effects of anabolic steroids show that they can cause various complications. In light of this, the present study aimed to evaluate the possible effects of the anabolic steroid Stanozolol on the cortical thickness of two brain areas (motor and limbic). For this study, brains of 28 adult male Wistar rats were analyzed, distributed into four groups (n=7) as follows: G1 – sedentary control group; G2 – control group + swimming; G3 – sedentary Stanozolol group; G4 – Stanozolol + swimming group. The animals were treated for 60 days, with doses administered twice a week with two-day intervals. The brains were processed following the standardized sequence in conventional histological procedures. The paraffin-embedded samples were cut with a thickness of 7μm using a Yide microtome and stained with hematoxylin-eosin (HE). Six areas of the cerebral cortex, three from each cerebral hemisphere (motor and limbic), were measured, and the values were recorded in µm2. Based on the main results of this study, it is observed that physical activity is a protective factor against the deleterious effects of the Stanozolol anabolic steroid on the cerebral cortex, while sedentary behavior is detrimental to the cortex thickness in both the sedentary control group and the sedentary Stanozolol group. It is concluded that the use of anabolic steroids in sedentary animals can lead to negative effects on limbic and motor cortical areas. On the other hand, physical exercise has been shown to be an important protective factor against the deleterious effects of the use of this anabolic steroid.